Clinical impact of the disposable ventouse iCup® versus a metallic vacuum cup: a multicenter randomized controlled trial. Issue 1 (December 2015) - Equy, Véronique; David-Tchouda, Sandra; Dreyfus, Michel; Riethmuller, Didier; Vendittelli, Françoise; Cabaud, Victoire; Langer, Bruno; Margier, Jennifer; Bosson, Jean-Luc; Schaal, Jean-Patrick
Abstract Background Assisted vaginal delivery by vacuum extraction is frequent. Metallic resterilizible metallic vacuum cups have been routinely used in France. In the last few years a new disposable semi-soft vacuum extraction cup, the iCup, has been introduced. Our objective was to compare maternal and new-born outcomes between this disposable cup and the commonly used Drapier-Faure metallic cup. Methods This was a multicenter prospective randomized controlled open clinical trial performed in the maternity units of five university hospitals and one community hospital in France from October 2009 to February 2013. We included consecutive eligible women with a singleton gestation of at least 37 weeks who required vacuum assisted delivery. Women were randomized tov acuum extraction using the iCup or usual Drapier-Faure metallic cup. The primary outcome was a composite criterion including both the risk of cup dysfunction and the most frequent maternal and neonatal harms: the use of other instruments after attempted vacuum extraction, caesarean section after attempted vacuum extraction, three detachments of the cup, caput succedaneum, cephalohaematoma, episiotomy and perineal tears. Results 335 women were randomized to the disposable cup and 333 to extraction using the metallic cup. There was no significant difference between the two groups for the primary outcome. However, failed instrumental delivery was more frequent in the disposable cup group, mainly due to detachment: 35.6 % vs 7.1 %, p < 0.0001. Conversely, perineal tears were more frequent in the metallic cup group, especially third or fourth grade perineal tears: 1.7 % versus 5.0 %, p = 0.003. There were no significant differences between the two groups concerning post-partum haemorrhage, transfer to a neonatal intensive care unit (NICU) or serious adverse events. Conclusions While the disposable cup had more detachments and extraction failures than the standard metallic cup, this innovative disposable device had the advantage of fewer perineal injuries. Trial registration www.clinicaltrials.gov :NCT01058200 on Jan. 27 2010.